Problems of small cities aglomeration – a case study Leibnitz - Florian, Martin; Tropper, Anton; Zsilincsar, Walter (Journal for Geography, 2006)
The study deals with the phenomenon of urban agglomeration, which so far could be observed only within of big and medium sized towns, nowadays is also including smaller central places of less than 10.000 inhabitants. Agglomeration nuclei like the district capital Leibnitz suffer from limited possibilities of expansion due to the small administrative area. This affects economic as well as demographic interests, and goes to the debt of the financial potential of core city, whereas the surrounding communities profits from economic expansion and population growth. The unification of the suburban communities with the central city would probably be the clearest reaction to the spatial structures. A good alternative to strengthen the interests of the whole agglomeration could be offered by means of an inter-communal financial compensation. The idea of a just distribution of financial burdens and yields resulting from economic investments, job creation, communal services, etc… among all communities of the agglomeration is just at its beginning.